Effects of Promotion and Price on the Purchasing Decisions of Herbs Product - Nani Nani; Umi Narimawati; Azhar Affandi; Heri Erlangga (Peneliti.net, 2022)
This study aims to determine the effect of promotion on purchasing decisions, determine the effect of price on purchasing decisions and the effect of promotion and price on purchasing decisions of herbal medicines at CV. Omar Smart Brain. The type of research used in this research is quantitative. The population in this study were consumers who shopped for herbal medicines at CV. Omar Smart Brain with a sample size of 100 customers using the slovin method. In collecting data using interview techniques and distributing questionnaires. The data analysis method used is multiple linear regression analysis, coefficient of determination, and coefficient significance test (t test and f test). The results showed that, partially the promotion variable has a significant effect on purchasing decisions by showing the results of the t-test = 4.657 while t-table = 1.98472 (tcount > ttable) with a significance level of 0.000. partially the price variable has a significant effect on purchasing decisions by showing the results of tcount = 3.632 while ttable = 1.98472 (tcount> ttable) with a significance level of 0.000. Simultaneously, promotion and price variables have a significant effect on purchasing decisions by showing Fcount = 60,461 which is greater than Ftable = 3,09 with a significance of 0,000. it can be said that promotion and price simultaneously have a significant effect on purchasing decisions. the coefficient of determination is obtained at 0.555, it can be concluded that promotion (X1) and price (X2) affect purchasing decisions (Y) by 55.50% while the remaining 44.50% is influenced by other factors not tested in this study. In this study, the results of the multiple linear regression coefficient of Y = 12,292 + 0,445X1 + 0,351X2+ e.